Le juge interne canadien et le droit international - Rigaldies, Francis; Woehrling, José (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
Given the almost total lack of constitutional or statutory provisions for the formulation and application of international law, Canadian courts have been invested with the basic responsibility for devising solutions to the problems that have arisen in this field. This paper examines how successful the courts have been as well as the way in which legal literature has reacted to their performance. It is the view of the authors that in dealing with international customary law, Canadian courts have applied solutions adapted from the law of Great Britain in a purely empirical way. While the absence of any theoretical framework has not been a crucial impediment until now, it is difficult to see how future problems can be resolved without any reference to basic principles. With respect to the interpretation and application of treaties, the transposition of principles derived from British practice to a federal context has been the source of notorious constitutional difficulties. Generally speaking, because of the traditional reverence accorded to the will of Parliamant, Canadian courts have been reluctant to recognize any measure of supremacy to international law.